Використання сайт-специфічної рекомбіназної системи Cre/loxP для отримання трансформантів Arabidopsis thaliana, вільних від маркерних послідовностей - Секан, А.С.; Ісаєнков, С.В.; Блюм, Я.Б. (Фактори експериментальної еволюції організмів, 2014)
Aims. One of the main issues in plant biotechnology is the development of marker-free genetically modified species that increase the consumer acceptance. One of the molecular tools that can help to resolve is site-specific recombination. We have developed a rapid and convenient DNA excision method mediated by the Cre/loxP recombination system. Methods. Analysis of stable transgenic Arabidopsis plants was determined by gistochemical analysis and PCR. Results. The aim of this study was to develop a novel Cre/loxP approach based on the cre gene expression. After expression recombinase could cause the excision of nptII marker gene and the Cre construct itself between the loxP sites. The excision event we examined by GUS staining. The results showed high level of unstained transgenes that could mean an excision event of target sequences. Conclusions. The development of efficient strategy to generate selectable marker-free transgenic plants could help increase the acceptance of genetically modified (GM) plants in community. Rapid and convenient DNA excision method mediated by the Cre/loxP recombination system was developed to produce marker-free transgenic plants without conditional treatment or the genetic crossing of offspring. Present study demonstrates that the novel site-specific recombinase Cre/loxP system provides a simple and efficient way to generate marker-free transgenic plants.

Key words: genetically modified plants, site0specific recombinase system, transformation by Agrobacterium tumefaciens, PCR analysis, GUS test.